A comparative study of Pakistani and British press regarding the framing of Afghanistan war 2001 (Journal of Governance and Development (JGD), 2014)
This study analyzed how Afghanistan war 2001 was framed by Pakistani and British press. What frames were employed by the newspapers of these two countries in the reporting of Afghanistan attack. For this purpose four newspapers were chosen from Britian and Pakistan namely The Dawn, The Nation, The Independent and The Guardian. The editorilas of these newspapers were analysed by employing the technique of thematic analysis. By analysing the data, it was found that Pakistani and British press mostly framed the coverage of Afghanistan war in a negative stance but at certain points Britsh press adopted positive or neutral stance. Anti war frame was dominnently employed by Pakistani newspapers but humanitrian and rebuilding frames were also observed. Likewise, Britsh press mostly covered Afghanistan under anti war frame but at some points pro war frame was also observed. Overall, it was noted that Pakistani press was more dominated by opposotional and critical themes than British newspapers.